2015
DOI: 10.1371/journal.pone.0119554
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Pro-Drinking Practices in Drinking Parents of Adolescents in Hong Kong

Abstract: Introduction and AimsParental alcohol-related practices are important risk factors of adolescent drinking, but little is known about the factors associated with these parental pro-drinking practices (PPDPs). We investigated the correlates of 9 PPDPs in drinking parents of adolescents in Hong Kong.MethodsA total of 2200 students (age 14.8±2.0; boys 63.2%) participated in a school-based cross-sectional survey in 2012. Analysis was restricted to 1087 (61.8%) students with at least 1 drinking parent as PPDPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We have also reported that Hong Kong parents with higher family affluence or parents who had higher education levels were more likely to mention the benefits of alcohol and that alcohol tastes good, and more willing to ask their children to open a bottle of alcohol and pour it. 36 Higher SES was also associated with binge drinking in the present study. It is unlikely that parents, especially those with high SES, would accept or encourage adolescent binge drinking.…”
Section: Discussionsupporting
confidence: 66%
“…We have also reported that Hong Kong parents with higher family affluence or parents who had higher education levels were more likely to mention the benefits of alcohol and that alcohol tastes good, and more willing to ask their children to open a bottle of alcohol and pour it. 36 Higher SES was also associated with binge drinking in the present study. It is unlikely that parents, especially those with high SES, would accept or encourage adolescent binge drinking.…”
Section: Discussionsupporting
confidence: 66%
“…It is possible that, compared to other substances, alcohol has less of a negative image and drinking might be perceived as more acceptable in higher SES groups. Other research has indicated that wealthier or more educated parents are more likely to talk positively about the taste or benefits of alcoholic drinks in front of their children [ 45 ]. As such, the use of substances by parents, as role models [ 46 ], may also provide some explanation for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Parental alcohol-related practices have been shown to be important risk factors for adolescent drinking. 19 In traditional Chinese culture, alcohol drinking is both a normal part of the daily diet, especially in rural areas, and an important part of rituals, business occasions, festivals and special events. Moderate drinking on important occasions is encouraged for adults, 20 and children may be given small amounts of alcoholic beverages by parents or grandparents, especially grandfathers.…”
Section: Introductionmentioning
confidence: 99%